2020
DOI: 10.2147/ijn.s258791
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optimized Nanostructured Lipid Carriers Integrated into In Situ Nasal Gel for Enhancing Brain Delivery of Flibanserin</p>

Abstract: Background and Aim: Flibanserin (FLB) is a multifunctional serotonergic agent used for treating hypoactive sexual desire disorder in premenopausal women via oral administration. FLB has a reported limited oral bioavailability of 33% that could be attributed to the drug's first-pass metabolism. In addition, FLB has a pH-dependent solubility that could be a challenging factor for drug dissolution in the body neutral fluid, and consequently, absorption via mucosal barriers. Thus, this work aims at investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Recently, various topically applied nanocarrier systems have been developed, including lipid based nanocarriers and polymer based nanocarriers, due to their unique advantages and great versatility as compared to conventional formulations [ 13 , 14 , 15 , 16 , 17 ]. In one of the studies, a nanosponge system was found to confine the drug into the pores of this system that showed a good availability of drugs, enhanced skin permeability and extended retention time at the site of application [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various topically applied nanocarrier systems have been developed, including lipid based nanocarriers and polymer based nanocarriers, due to their unique advantages and great versatility as compared to conventional formulations [ 13 , 14 , 15 , 16 , 17 ]. In one of the studies, a nanosponge system was found to confine the drug into the pores of this system that showed a good availability of drugs, enhanced skin permeability and extended retention time at the site of application [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…EM-NLCs-opt and EM-NLCs-opt-IG4 showed significantly higher release of EM due to the increase in the solubility of EM in the presence of the lipid and surfactant. The drug release from EM-IG was found to be significantly low due to the poor solubility of EM, high viscosity, and formation of insoluble gel matrix hindering the release of EM in STF media [ 45 ]. The release data of the EM-NLCs-opt-IG4 were fitted in different kinetic models to determine the best fit model.…”
Section: Resultsmentioning
confidence: 99%
“…This could be owing to the cavitation forces developed by the ultrasonic waves of the sonicator. These forces might cause particle size reduction by virtue of possible fractionation of the agglomerated nanoconjugate clusters [ 42 , 43 ]. A minimized particle size of the prepared ALS-MP formula was achieved as a result of the application of experimental design in drug formulation.…”
Section: Discussionmentioning
confidence: 99%